Association between weight-bearing ankle dorsiflexion range of motion during deep squat sitting and quality of life after ankle fracture surgery: a cross-sectional study - Miyasaka, Hayato; Ebihara, Bungo; Fukaya, Takashi; Iwai, Koichi; Kubota, Shigeki; Mutsuzaki, Hirotaka (Frontiers in Rehabilitation Sciences, 2025)
BackgroundAnkle fracture is a common type of trauma. Although ankle fractures reduce the quality of life (QOL), few studies have investigated this factor, and even fewer have investigated the impact of postoperative physical function on reduced QOL. We aimed to clarify the physical factors that affect the QOL after ankle fracture surgery.MethodsThis cross-sectional study included 32 patients who underwent surgery for ankle fractures. QOL was assessed using the Self-Administered Foot Evaluation Questionnaire (SAFE-Q). Ankle dorsiflexion range of motion (ROM) was measured with and without weight bearing. The weight-bearing ankle dorsiflexion ROM was measured using four methods: measuring the rear ankle with the knee extended and flexed, measuring the front ankle, and measuring the ankle during deep squat sitting. Gait parameters were measured using a three-dimensional motion analyzer. Multivariate analysis was performed using the four subscales of the SAFE-Q (pain and pain-related, physical functioning and daily living, social functioning, and general health and well-being) as dependent variables.ResultsThe multivariate analysis revealed that weight-bearing ankle dorsiflexion ROM during deep squat sitting was an independent variable for pain and pain-related [standardized partial regression coefficient (β) = 0.584, P < 0.001], physical functioning and daily living (β = 0.376; P = 0.006), social functioning (β = 0.317; P = 0.045), and general health and well-being (β = 0.483; P = 0.005). Gait speed was selected as an independent variable for physical functioning and daily living (β = 0.555; P < 0.001) and social functioning (β = 0.514; P = 0.002).ConclusionsWeight-bearing ankle dorsiflexion ROM during deep squat sitting and gait speed were associated with QOL of patients after ankle fracture surgery. These findings may inform treatment programs to improve QOL after ankle fractures and provide the theoretical background necessary for the development of new treatments.